Community Empowerment Through Herbal Drink Creation as An Effort to Develop the Creative Economy - Dina Anggraeni Susesti; Eny Dyah Yuniwati; Novi Rahmania Aquariza (Pascasarjana Universitas Mataram, 2025)
Community empowerment through the creation of herbal beverages is an effective strategy for developing a sustainable creative economy. Herbal beverages, as products that combine cultural heritage with modern innovation, have great potential to create added value and open new business opportunities at the local level. Through training in the processing, marketing, and management of herbal beverage businesses, communities not only acquire new skills but also are able to independently increase their income. This empowerment program focuses on increasing human resource capacity, utilizing local raw materials, and developing products that meet market tastes and current health trends. In addition to the economic aspect, this activity also helps maintain environmental sustainability and preserve local wisdom. Herbal beverage-based empowerment supports the creation of a dynamic and competitive local entrepreneurial ecosystem, while strengthening community social networks.